Предмет: Алгебра, автор: strangersh

sqrt(x+3-4*sqrt(x-1))+sqrt(x+8-6*sqrt(x-1))=1

Ответы

Автор ответа: Юленька194
5
 \sqrt{x+3-4 \sqrt{x-1}}+ \sqrt{(x+8-6 \sqrt{x-1}}=1
 \sqrt{x+(4-1)-4 \sqrt{x-1}}+ \sqrt{(x+(9-1)-6 \sqrt{x-1}}=1
 \sqrt{x-1-4 \sqrt{x-1}+4}+ \sqrt{(x-1-6 \sqrt{x-1}+9}=1
 \sqrt{( \sqrt{x-1})^2-2*2 \sqrt{x-1}+2^2}+ \sqrt{ (\sqrt{x-1})^2-2*3 \sqrt{x-1}+3^2}=1
 \sqrt{( \sqrt{x-1}-2)^2}+ \sqrt{ (\sqrt{x-1}-3)^2}=1
| \sqrt{x-1}-2|+ |\sqrt{x-1}-3|=1
ОДЗ: x-1 \geq 0 \\ x \geq 1


2 \leq  \sqrt{x-1}  \leq 3 \\ 4 \leq x-1 \leq 9 \\ 5 \leq x \leq 10
Ответ: [5;10]
Похожие вопросы
Предмет: Химия, автор: dashab15022007